Characterizing alternating bubbles emerging from two interacting vertical gas jets in a liquid. (2nd February 2022) - Padash, A.; Chen, B.; Boyce, C.M.
Graphical abstract: Highlights: Bubbles from two jets break off in an alternating pattern under certain conditions. We develop a harmonic oscillator model to capture this behavior. When bubbles coalesce, they break off simultaneously. We map regimes based on the ratio of bubble diameter to jet separation distance. Abstract: Optical imaging experiments were conducted to investigate regimes of bubbling when two vertical gas jets are injected into liquids. Three regimes were identified (i) bubbles break off from jets independently of one another, (ii) bubbles coalesce and break off from jets at the same time and (iii) bubbles break off from jets in an alternating pattern, nearly 180 degrees out-of-phase from one another. We identify that a mixed capillary number is key to determining the size of bubbles. Further, we find that the ratio of bubble diameter at breakoff to separation distance between jets is key to determining the regime of bubble breakoff. The alternating pattern is attributed to a growing jet pushing liquid between the two jets towards the second jet, such that the second jet pinches off, forming a bubble. This mechanism is used to formulate a simplified coupled harmonic oscillator model which captures alternating bubbling.